2013
DOI: 10.5194/hessd-10-3103-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-stationary flood frequency analysis in continental Spanish rivers, using climate and reservoir indices as external covariates

Abstract: Recent evidences of the impact of persistent modes of regional climate variability, coupled with the intensification of human activities, have led hydrologists to study flood regime without applying the hypothesis of stationarity. In this study, a framework for flood frequency analysis is developed on the basis of a tool that enables us to address the modelling of non-stationary time series, namely, the "generalized additive models for location, scale and shape" (GAMLSS). Two approaches to non-stationary … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
103
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 63 publications
1
103
0
Order By: Relevance
“…urbanisation, regulation of rivers, construction of dikes, deforestation, etc.) (Coles, 2001;Lopez and Frances, 2013;Merz et al, 2012;Prosdocimi et al, 2015;Salas and Obeysekera, 2014;Strupczewski et al, 2001;Villarini et al, 2009;Vogel et al, 2011). Recently, more attention has been paid to non-stationary frequency estimation of flood extremes.…”
Section: Introductionmentioning
confidence: 99%
“…urbanisation, regulation of rivers, construction of dikes, deforestation, etc.) (Coles, 2001;Lopez and Frances, 2013;Merz et al, 2012;Prosdocimi et al, 2015;Salas and Obeysekera, 2014;Strupczewski et al, 2001;Villarini et al, 2009;Vogel et al, 2011). Recently, more attention has been paid to non-stationary frequency estimation of flood extremes.…”
Section: Introductionmentioning
confidence: 99%
“…Some GAMLSS applications in hydrological/climatological time-series are presented by Villarini et al (2009aVillarini et al ( , b, 2010aVillarini et al ( , b, 2012, Machado et al (2015), López and Francés (2013), Osorio and Galiano (2012), Hudson et al (2008). GAMLSS have been used to model seasonal rainfall and temperature in Rome by Villarini et al (2010a); they showed that the GAMLSS models could represent the magnitude and spread in the seasonal time series with parameters being a smooth function of time or teleconnection indices.…”
Section: Hydrological Applications and Assessment Of The Gamlss Softwarementioning
confidence: 99%
“…GAMLSS have been used to model seasonal rainfall and temperature in Rome by Villarini et al (2010a); they showed that the GAMLSS models could represent the magnitude and spread in the seasonal time series with parameters being a smooth function of time or teleconnection indices. GAMLSS models have been used for flood frequency analysis in Villarini et al (2009a, b) and López and Francés (2013). The study by Machado et al (2015) also applied GAMLSS to model flood data using historical information.…”
Section: Hydrological Applications and Assessment Of The Gamlss Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…In studying flow series, Bernier (1959) showed that the Frechet distribution is better than the Gumbel distribution at fitting extreme values. Other distributions are best suited to the modelling of maximum flow rates, such as the generalized extreme value (GEV) distribution in Great Britain, the log-normal distribution in China, the log-Pearson type III distribution in the USA (Bobée, 1999), the gamma distribution in central and Eastern Algeria (Hebal et al, 2011a(Hebal et al, , 2011b) and the log-normal distribution in the Chellif Basin of Algeria (Achite and Meddi, 2004), the gamma distribution in Morocco (Riad et al, 2006) and Spain (López and Francés, 2012), the generalized normal (GNO) distribution for Northern Tunisia and both the GEV and GNO distributions for Central and Southern Tunisia (Ellouze and Abida, 2008).…”
Section: Introductionmentioning
confidence: 99%